Psychometric properties of the Italian adaptation of the Mor Barak et al. diversity climate scale - Paolillo, A.; Pasini, M.; Silva, S. A.; Magnano, P. (Quality and Quantity, 2017)
The Diversity Climate Scale is a questionnaire developed in the U.S. for the investigation of employees’ shared perceptions about their organizational context related to women and minorities. The measure was not used in the European context yet. The psychometric properties of the Italian adaptation of the Mor Barak, Cherin and Berkman Diversity Climate Scale were investigated in this work by using a sample of Italian (n = 395) white-collar and blue-collar employees. A pilot study to make the scale suitable for the Italian context was conducted using the cognitive interview technique. Then a series of multiple-group confirmatory factor analyses was performed. The results showed that a three-factor solution best fit the data, using only 12 items of the original scale. The analyses supported factor variance and factor covariance equivalence in addition to metric equivalence. Internal consistency of the scale was good. Discriminant validity between latent factors and Criterion validity were supported.